Effects of autumn tillage with straw return on soil physical characteristics of corn fields in the eastern loess plateau - Fan, Yuchen; Yuan, Yaqi; Li, Tao; Lin, Wen; Tang, Xiwang; Liang, Gaimei; Li, Nana (Frontiers in Environmental Science, 2024)
Unreasonable tillage practices destroy the structure of the ploughed layer and affect soil physical parameters. Applying a reasonable tillage method allows improved soil physical quality. Three autumn tillage practices, i.e., autumn no-tillage with straw mulch (NTS), autumn rotary tillage with straw incorporation (RTS), and autumn plough tillage with straw incorporation (PTS), have been carried out at the Dongyang Experimental Station of Shanxi Agricultural University since 2016. The impact of autumn tillage practices on soil physical quality in the 0-30 cm profile of spring corn fields was assessed after the corn harvest in 2018 and 2019.